PENGENDALIAN HAMA BUBUK KEDELAI (Callosobruchus analis F.) DENGAN BIJI SIRSAK (Annona muricata) - Harinta, Yos Wahyu; R., Nugraheni; Setyorini, Agung (Jenderal Soedirman University, 2016)
The aim of this research is to know the influence of the flour soursop seed of the controlling pestCallosobruchus analis at the soursop seed. This research has been implemented experimentally, consists of twophases. The first is to know the effectivity of the flour soursop seed against mortallity of the beetle C. analis. andthe laying of eggs, while the second phases is to know the influence of the flour soursop seed against the influenceof the beetle population C. analis. This research has used RAL/CRD/ Completely Randomized Design with onetreatment factor that is : the dosege of the flour soursop seed,consiste of A) the flour soursop seed, dosege 1,50g/100g ; B) the flour soursop seed, dosage 1,00 g/100 g ; C) the flour soursop seed, dosage 0,50 g/ 100 g; O)Control/without treatment. Every tretment is repeated five time. The observation of the parameter is : mortalityand development of the beetle C. analis, the percentageof the seed damage and the decrease of the seed heavy.The result of this research indicated that; the flour soursop seed influenced for the mortality and devolepment C.analis at the soy bean seed; the flour soursop seed can reduce for damage and the decrease of the seed heavyagainst attacking C. analis. The effective dosage of the flour soursop seed for controlling the beetls C. analis, isnot founded yet. From the result of this research, can be concluded that the flour soursop seed by dosage 1,50 g/100 g seed can influence for increasing mortality and decreasing the expansion of the beetle powder C. analis atthe say been seed and can reducing the damage and the decreasing the soy bean seed heavy because of theattacking the powder of beetle C. analis at storaging, the effective dosage of the flour soursop seed for controllingthe beetle C. analis is not founded yet.Keywords: the flour soursop seed (Annona muricata), the powder of beatle Callosobruchus analis F.Â ABSTRAKPenelitian bertujuan untuk mengetahui pengaruh tepung biji sirsak terhadap pengendalian hamaCallosobruchus analis pada biji kedelai. Penelitian ini dilaksanakan secara eksperimen, yang terdiri dari dua tahap,tahap pertama adalah mengetahui efektifitas tepung biji sirsak terhadap mortalitas kumbang C. analis danpeletakan telur sedangkan tahap kedua mengetahui pengaruh tepung biji sirsak terhadap perkembangan populasikumbang C. analis. Penelitian menggunakan Rancangan Acak Lengkap (RAL/CRD) dengan 1 faktor perlakuanyairu dosis tepung biji sirsak. Adapun dosis perlakuan adalah dosis tepung biji sirsak yang terdiri dari (A) Tepungbiji sirsak , dosis 1,50 g / 100 g; (B) Tepung biji sirsak, dosis 1,00 g / 100 g; (C) Tepung biji sirsak , dosis 0,50 g/ 100 g; (O) Kontrol / Tanpa Perlakuan. Tiap Perlakuan diulang lima kali. Parameter pengamatan adalah ;mortalitas dan perkembangan kumbang C. analis, persentase kerusakan biji dan penyusutan bobot biji. Hasilpenelitian menunjukkan bahwa tepung biji sirsak berpengaruh terhadap mortalitas dan perkembangan C. analispada biji kedelai ; tepung biji sirsak dapat mengurangi terhadap kerusakan dan penyusutan bobot biji kedelaiterhadap serangan C. analis; belum didapat dosis tepung biji sirsak yang efektif untuk mengendalikan kumbangC.analis. Dari hasil penelitian, dapat disimpulkan bahwa tepung biji sirsak dengan dosis 1,50 g / 100 g biji dapatberpengaruh terhadap peningkatan mortalitas dan penurunan perkembangan kumbang bubuk Callosobruchusanalis F. pada biji kedelai serta dapat mengurangi kerusakan dan penyusutan bobot biji kedelai akibat serangankumbang bubuk Callosobruchus analis F. di penyimpanan, namun belum didapat dosis tepung biji sirsak yangefektif untuk mengendalikan kumbang C. analis F.Kata kunci: Tepung biji sirsak (Annona muricata), Kumbang bubuk Callosobruchus analis F.